Analisis Vibrasi pada Pompa Motor Air di PT Krakatau Tirta Industri Cilegon - Muhammad Yusuf Habibi; Irwanto Irwanto (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
The primary coolant pump is a critical component in ensuring safe and reliable reactor operation. Therefore, early detection of the type and severity of damage affecting its constituent components is essential. Among the main parts of the pump, bearings are components that frequently experience deterioration or failure during operation. Bearing damage is generally indicated by abnormal vibration levels or an increase in bearing temperature. This study aims to identify the symptoms of bearing damage and determine the level of damage through vibration analysis. Early signs of pump malfunction can be detected by continuously monitoring the vibration response using a vibration tester. The measurement process is carried out in three directions, namely radial, axial, and tangential, to obtain a comprehensive description of the vibration behavior of the bearing. The vibration data are then analyzed to identify characteristic peaks associated with possible bearing defects. Through this analysis, the condition of the bearing can be evaluated more accurately, enabling maintenance personnel to recognize developing damage at an early stage. The results are expected to support preventive maintenance activities and reduce the risk of unexpected pump failure during reactor operation.